2017
DOI: 10.1039/c6qm00286b
|View full text |Cite
|
Sign up to set email alerts
|

Controlled self-aggregation of perylene bisimide and its application in thick photoconductive interlayers for high performance polymer solar cells

Abstract: Highly conductive cathode interlayers are essential important for polymer solar cells that can work efficiently when the film is thick, which facilitates the massive production in future. Herein, an asymmetric organic dye molecule, perylene bisimide (PBI) 3, is synthesized as the photosensitizer for zinc oxide (ZnO) to achieve photoconductive hybrid material. The self-aggregation of PBI3 was efficiently restricted by the introduction of an alkyl group at one of the imide position in the molecule structure, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Zhao et al showed that an asymmetric PBI enhanced the photoconductivity when used to dope the ZnO layer and this contributed to increased efficiency of PTB7/PC 71 BM based OPVs. 44 When the photoconductivity of the amino acid appended PBIs was studied, PBI-F, PBI-Y and PBI-W showed the lowest photoconductivity, indicating that radical anions (or dianions) were not readily formed under illumination. 24 Notably, it is these materials that are used in the highest performing OPV devices, and indeed exhibit the highest open-circuit voltages.…”
Section: Resultsmentioning
confidence: 99%
“…Zhao et al showed that an asymmetric PBI enhanced the photoconductivity when used to dope the ZnO layer and this contributed to increased efficiency of PTB7/PC 71 BM based OPVs. 44 When the photoconductivity of the amino acid appended PBIs was studied, PBI-F, PBI-Y and PBI-W showed the lowest photoconductivity, indicating that radical anions (or dianions) were not readily formed under illumination. 24 Notably, it is these materials that are used in the highest performing OPV devices, and indeed exhibit the highest open-circuit voltages.…”
Section: Resultsmentioning
confidence: 99%
“…In this respect, perylenebisimide (PBI)i sa ni nteresting chromophored ue to its excellent thermala nd opticals tabilities, [59,60] high molar absorption coefficient, [61] reversible redox properties, [48,[62][63][64][65] and feasible derivatization chemistry. [66] These features make PBI av ersatile chromophorei nt he field of photovoltaics, [67] artificial photosynthesis, [68] and CS studies. [64,[69][70][71][72] However,m ost of the previouss tudies focusedo n the fluorescent properties of the PBI chromophore, and its triplet-state behavior remainsu nrevealed to alarge extent.…”
Section: Introductionmentioning
confidence: 99%
“…Among the ZnO-based organic-inorganic hybrids, perylene/ZnO hybrids as photoconductive hybrid materials were intensively studied [14][15][16][17][18] and showed very promising applications as cathode interlayer for high-performance solar cells. However, it is still challenging to obtain highly dispersed (molecular level) perylene/ZnO hybrids due to strong pi-pi stacking of perylene-induced phase separation between perylenes and ZnO [19]. On another hand, molecular level hybridization between perylene and ZnO will be helpful for efficient charge transfer in the hybrids, which has a large impact on photovoltaic property of materials, which is therefore essential to their applications in photovoltaics field [20][21][22].…”
Section: Introductionmentioning
confidence: 99%